2018
DOI: 10.1002/jum.14660
|View full text |Cite
|
Sign up to set email alerts
|

Acute Acalculous Cholecystitis in Hospitalized Patients With Hematologic Malignancies and Prognostic Importance of Gallbladder Ultrasound Findings

Abstract: Symptomatic patients who meet the US criteria for the diagnosis of AAC have a poor prognosis. Other patients require a close follow-up US examination within 1 week to detect early progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
(34 reference statements)
2
5
0
Order By: Relevance
“…On the other hand, the lower complication rate and shorter duration of symptoms may also attribute to early diagnosis and treatment in this group. This is in line with a study by Thampy et al (21), which found that 41% of the patients in the AAC (-) group had positive results for AAC within 1 week of the follow-up ultrasound. Due to the rapid progression of AAC, the role of ultrasound follow-up has been emphasized for the early detection of progressed AAC as well as to prevent misdiagnoses and missed diagnoses (19).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the lower complication rate and shorter duration of symptoms may also attribute to early diagnosis and treatment in this group. This is in line with a study by Thampy et al (21), which found that 41% of the patients in the AAC (-) group had positive results for AAC within 1 week of the follow-up ultrasound. Due to the rapid progression of AAC, the role of ultrasound follow-up has been emphasized for the early detection of progressed AAC as well as to prevent misdiagnoses and missed diagnoses (19).…”
Section: Discussionsupporting
confidence: 92%
“…The higher incidence rate observed in our study agrees with previous studies (18)(19)(20). For example, a previous study found that among 94 patients with hematological malignancies and clinical manifestations, the AAC (+) group often presented with a higher rate of complications and mortality (20.9%) than the AAC (-) group (0%; P < 0.001) (21).…”
Section: Discussionsupporting
confidence: 91%
“…Other risk factors that increase the risk of AAC are immunodeficiencies, atherosclerosis, vasculitis, diabetes mellitus, stroke, arterial hypertension, factors reducing vagal tone, bone marrow transplantation, interleukin-2 therapy, and lymphokine-activated killer cell therapy [ 35 , 78 , 79 , 80 , 81 , 82 , 83 ].…”
Section: Aac Pathogenesismentioning
confidence: 99%
“…Diagnostic evaluation usually includes an US or a cholescintigraphy nuclear scan (HIDA). Another imaging method sometimes used is CT scan [68,69].…”
Section: Acalculous Cholecystitismentioning
confidence: 99%